Comprehensive solution of logistics problem of ensuring the life of population in emergency situations (Science journal «Technical service of agriculture, forestry and transport systems», 2025)
The work considers the urgent problem of timely and effective provision of food and staff of the State Emergency Service in the territories that are victims of emergencies. On the basis of an analysis of a number of publications, it is shown that most deaths in the process of natural catastrophes are caused not by direct striking factors, but by hunger and epidemics that occur in the respective territory. There are also many facts about the negative effects on the health of the most vulnerable categories of the population (children, elderly, people suffering from chronic diseases, etc.) of long, more than twenty -one days, nutrition with high -energy fruit pastes, cookies, and standard army diet. The example of the US and Japan shows cases of detection of significant food reserves in stores warehouses that have not been used in the process of eliminating the consequences of emergencies. To prevent this phenomenon, it is proposed to use centralized preparation and nutrition of the population using army field kitchens. To use them, you need to have enough products and recipe for hot dishes. Generally, this task was called linear programming problem. A numerical example of its solution is given.This approach provides an opportunity to make regulatory calculations necessary to determine the amount of inventories of products in case of emergencies. The developed diet uses only local and public products. Since, in emergency situations, decisions are made in conditions of incomplete information, the methods of stochastic linear programming were used to optimize logistics processes. To solve the problem of the diet, it is accepted that the distribution of the parameters of the problem is uniform. To optimize the fuel costs required for the delivery of consumption products, a linear programming transportation problem was solved in deterministic and stochastic variants.
Keywords: emergency situations; food provision in emergency foods; linear programming; stochastic linear programming; diet task; transport problem